THE APPLICATION OF PROJECT BASED LEARNING (PjBL) MODEL ON STUDENT LEARNING OUTCOMES OF BIODIVERSITY MATERIAL - Mahzura, Jihan Pradita; Pranoto, Hendro (Universitas Negeri Medan, 2025)
The purpose of this study was to see the application of the PjBL model on student learning outcomes of biodiversity material in class X SMAN 19 Medan. This research used pre-experiment with one group pretest-posttest design. The sample was taken by random sampling technique, namely class X-8. Data collection to measure learning outcomes used multiple choice questions and observation sheets. The results showed an increase in cognitive learning outcomes with n-gain 0.62 (medium category), as well as affective and psychomotor outcomes in the good category. In conclusion, the application of theh PjBL model is able to improve cognitive, affective and psychomotor learning outcome.